2015
DOI: 10.1093/mnras/stv498
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on particle acceleration sites in the Crab nebula from relativistic magnetohydrodynamic simulations

Abstract: The Crab Nebula is one of the most efficient accelerators in the Galaxy and the only galactic source showing direct evidence of PeV particles. In spite of this, the physical process behind such effective acceleration is still a deep mystery. While particle acceleration, at least at the highest energies, is commonly thought to occur at the pulsar wind termination shock, the properties of the upstream flow are thought to be non-uniform along the shock surface, and important constraints on the mechanism at work c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 49 publications
4
79
0
Order By: Relevance
“…2 we show how the simulated synchrotron map changes due to the inclusion of a small scale fluctuating magnetic field. The model is the one described in Olmi et al (2015), and targeted to the Crab nebula. For reference to the fully ordered case (σ = 0) one should take Olmi et al (2015), but for σ raising from 0.3 at r = 0.6 ly to 1 at r = 1.25 ly.…”
Section: Emission Mapsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 we show how the simulated synchrotron map changes due to the inclusion of a small scale fluctuating magnetic field. The model is the one described in Olmi et al (2015), and targeted to the Crab nebula. For reference to the fully ordered case (σ = 0) one should take Olmi et al (2015), but for σ raising from 0.3 at r = 0.6 ly to 1 at r = 1.25 ly.…”
Section: Emission Mapsmentioning
confidence: 99%
“…The model is the one described in Olmi et al (2015), and targeted to the Crab nebula. For reference to the fully ordered case (σ = 0) one should take Olmi et al (2015), but for σ raising from 0.3 at r = 0.6 ly to 1 at r = 1.25 ly. Color-scale normalized to the maximum.…”
Section: Emission Mapsmentioning
confidence: 99%
See 1 more Smart Citation
“…This supports the Schweizer et al (2013) findings (based on earlier optical and X-ray monitoring) who concluded that the X-ray and optical emission must be produced by different populations of particles. Furthermore, according to Schweizer et al (2013), the fits with the Doppler-boosted tilted ring model require noticeably different (higher) flow velocities for the optical wisps (≈ 0.9c) compared to the X-ray wisps, which made Schweizer et al (2013) question the simple "boostedring" model (see, however, Olmi et al 2015). K+15 also found that for most individual features of the PWN (e.g., wisps) the NIR-optical-FUV spectra are harder than the contemporaneously measured X-ray spectra suggesting either an additional narrow spectral component or other kind of complex behavior between optical and soft X-rays.…”
Section: Multiwavelength Properties Of the Crabmentioning
confidence: 99%
“…In the MHD simulations these features are formed due to the combination of flow dynamics (i.e. fluid vortices produced near the TS due to magnetosonic oscillations; see e.g., (Olmi et al 2015) and references therein) and Doppler boosting. The emission from the oblique termination shock that has been also associated with the Crab's Inner Knot (Komissarov and Lyubarsky 2003;Yuan and Blandford 2015;see, however Melatos et al 2005 and references therein for alternative interpretations).…”
Section: Multiwavelength Properties Of the Crabmentioning
confidence: 99%